'The Town is Surrounded:' From Climate Concerns to life under Wind Turbines in La Ventosa, Mexico. Issue 2 (July 2017) - Dunlap, Alexander
The Isthmus of Tehuantepec region of southwest Oaxaca, Mexico, known locally as the Istmo, was identified in 2003 as a prime site for wind energy development. Supported by climate change mitigation legislation, a 'wind rush' engulfed the Istmo. Now, La Ventosa sits surrounded by high-tension wires and wind turbines, some only 280 meters from homes. This paper argues that new valuations of wind resources based on market mechanisms and anthropogenic climate change laws are intensifying the destructive trajectory of the industrial economy. There are benefits for land owners and political authorities, and what amounts to token civil works projects for the town. But the majority of people interviewed expressed dissatisfaction towards the existence of wind parks surrounding the town. Instead of collective benefits, the wind parks brought different degrees of health concerns, enormous increases in land, rent, food, and electricity prices, as well as insecurity. The findings here demonstrate that wind energy development, encouraged by climate change mitigation policies, is intensifying pre-existing trends towards inequality and poverty in La Ventosa. Meanwhile, the destructive operations of the global industrial economy are renewed, using market-based approaches to mitigating anthropogenic climate change.